18 Transoesophageal echo in the investigation of cryptogenic stroke and transient ischaemic attack – diagnostic yield and impact on clinical management. (7th October 2015) - McClelland, S; Hennessey, B; Fitzpatrick, N; Collison, D; Giblin, G; Hussein, H; Salim, T; Foley, D; McAdam, BF
Abstract : Introduction: Transoesophageal echocardiography (TOE) is commonly performed in the investigation of ischaemic stroke/TIA. Previous studies have suggested a high yield of potentially significant clinical findings, but a wide variation in impact on clinical management. Aim: To examine the diagnostic yield of TOE in patients referred for investigation of ischaemic stroke/TIA in a single centre and to determine the impact of these findings on clinical management. Methods: 108 consecutive patients undergoing TOE for investigation of ischaemic stroke/TIA between July 2014 and April 2015 were identified. TOE reports, MRI/CT brain reports and clinical discharge summaries were reviewed for each patient. Results: 108 patients were identified. 74 were male (68.5%). Average age was 54.9 ± 13.3 years. The majority (77.8%) were aged ≤65 years. Average age in the "young CVA/TIA" cohort was 50 ± 10.3 years (range 21–65). 88 patients (81.5%) had CT/MRI-confirmed infarcts. 6 patients (5.6%) were in atrial fibrillation at the time of TOE. 17 patients (15.7%) had recurrent events and 18 (16.7%) had bilateral infarcts. At least one potentially significant finding was detected in 86 patients (79%). Interatrial septum: Patent foramen ovale (PFO) was detected by colour flow in 48% of patients and right to left shunt demonstrated by bubble study in 84.6% of these cases. Interestingly, the prevalence of PFO did not differ between the "young stroke" cohort and the older age group (47% and 48%, respectively). Atrial septal aneurysm was detected in 12 patients (11.1%), all of whom had PFO. 3 patients who previously had device closure of PFO were investigated for symptom recurrence. Residual right to left shunt was demonstrated in one of these cases. Left ventricle: 11 patients had impaired LV systolic function (10.2%), 4 with EF ≤ 35%. Mural thrombus was identified in one patient. Left atrium (LA)/Left atrial appendage (LAA): Significant LA dilatation was identified in 23 patients (21.3%). This was more prevalent in the older age group. Spontaneous echocontrast was visualised in 3 cases (2.8%), two of whom were aged >65 years. LAA prethrombus/thrombus were detected in two older patients (1.9%). Valvular abnormalities: Valvular abnormalities were detected in 40 patients (37%). Valvular echodensities were visualised in 28 patients. The majority were degenerative, while one patient was diagnosed with infective endocarditis. 7 patients had significant mitral regurgitation (6.5%) and one patient had mechanical mitral valve thrombus. Aortic atheroma: 32 patients had Grade II or higher aortic atheroma (29.6%), which was more prevalent in the older age group. Two patients had grade V aortic atherosclerosis. Impact on clinical management: Clinical management was changed in 21 (19.4%) patients on the basis of TOE findings alone. The majority of these changes (13 patients, 12%) involved insertion of or referral for device-occlusion of PFO. No patient >65 years was referred for PFO closure. One patient was referred for LAA occlusion. Three (2.8%) were anticoagulated on the basis of TOE findings alone. An alternative/competing mechanism for stroke/TIA was subsequently identified in 20.4% of patients. Conclusion: The diagnostic yied of TOE in ischaemic stroke/TIA in this cohort was high with a potentially significant abnormality identified in 79% of patients. Where management was changed as a result (19.4% of patients), the majority were referred for device closure of PFO in the younger population.